Pesan Moral dalam Konten TikTok Polisi @hermanhadibasuki (Analisis Semiotik Ferdinand de Saussure) - Ryan Adam; Andries Lionardo; Ramdan Lamato (Penerbit Goodwood, 2023)
Purpose: Semiotics is a method of studying a sign and its representations. In this research, TikTok content video contain sign that appear and produce the meaning of the moral message in the content video. The Purpose of this research is to determine the signified and signifier in the moral message in TikTok Police Content @hermanhadibasuki. Research methodology: The research method used in this research is qualitative method with a descriptive approach. The data collection techniques in this research used a documentation and literature studies, as well as references related to this research. Results: The result of the research show that there is a moral message in TikTok Police Content @hermanhadibasuki (Ferdinand de Saussure Semiotic Analysis). The result of this research where examination several scene video who describing the moral message for the audiences. Saussure divides a sign into two aspects, that is signifier which is seen through the physical form and form of the research object and signified which is related to social life. This research used social media TikTok to share a video content who has a moral message in it. Limitation: The limitation in this research is in the research process. One of the limitations is that the researchers would have to choose from many videos uploaded by the TikTok creator. Contribution: This research can be useful for the student or an academic community who want to know and to do the similar research on semiotics.